Empirical nursing : the art of evidence-based care - Garrett, Bernie (Bingley, U.K. : Emerald Publishing Limited, 2018)
This book seeks to provide students and practicing nurses with the tools to better understand and engage in scientific arguments to support quality nursing and evidence-based practice. The nature of nursing and its relationship with science remains an area of ongoing debate, controversy and considerable confusion to both students and practitioners. For a science-based health discipline, it is something of a paradox that most nursing students have limited exposure to scientific philosophy education, which is not covered in depth in many modern university nursing programmes. This work seeks to remedy this: in providing material on modern scientific research methods, with particular emphasis on the context of practice, it presents an alternative theoretical iteration of holistic nursing as scientific inquiry. The author is a passionate advocate for empirical and pragmatic approaches to nursing, and the book provides challenging ideas to support a new wave of critical-thinking in contemporary nursing, confronting postmodern dogma with contemporary scientific critique. In doing so, this text engages readers with the art of progressive empirical client-centred care, appropriate for the development of 21st century holistic nursing practice.
Includes bibliographical references and index.
Print version record
Keywords: Evidence-based nursing; Evidence-based medicine; Medical, Nursing -- Management & Leadership; Nursing management & leadership